2016
DOI: 10.1007/s12035-016-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Omics to Explore Amyotrophic Lateral Sclerosis Evolution: the Central Role of Arginine and Proline Metabolism

Abstract: In amyotrophic lateral sclerosis (ALS), motor neuron degeneration is associated with systemic metabolic impairment. However, the evolution of metabolism alteration is partially unknown and its link with disease progression has never been described. For the first time, we ran a study focused on (1) the evolution of metabolism disturbance during disease progression through omics approaches and (2) the relation between metabolome profile and clinical evolution. SOD1-G93A (mSOD1) transgenic mice (n = 11) and wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 68 publications
4
38
0
Order By: Relevance
“…However, clinical studies have provided conflicting evidence with some studies reporting negative effects or a lack of efficacy [ 49 , 50 , 51 ], whereas others reported amelioration of ALS symptoms [ 52 , 53 ]. More recently, in vivo preclinical evidence suggests that BCAA, tryptophan, and particularly arginine and proline metabolic pathways are associated with disease progression [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies have provided conflicting evidence with some studies reporting negative effects or a lack of efficacy [ 49 , 50 , 51 ], whereas others reported amelioration of ALS symptoms [ 52 , 53 ]. More recently, in vivo preclinical evidence suggests that BCAA, tryptophan, and particularly arginine and proline metabolic pathways are associated with disease progression [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have addressed whether AA metabolism is crucial for HCC tumor progression. Arginine and proline metabolisms are the central pathway for the biosynthesis of AAs from glutamate (24). Recently, proline metabolism has been shown to be critical for tumor Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…In the aspect of pathway analysis, Patin et al highlighted that arginine-proline, tryptophan, and branched amino acid metabolic pathways were associated with ALS evolution. 24 In this study, we also identified several amino acid metabolism-related pathways, including phenylalanine-tyrosine-tryptophan biosynthesis, aminoacyl-tRNA biosynthesis, and phenylalanine metabolism. The mechanisms underlying the disturbed amino acid metabolisms to ALS still need further investigations.…”
Section: Discussionmentioning
confidence: 99%